Work Placements in Masters of Translation: Five Case Studies from the University of Western Australia - Jaccomard, Hélène (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
In Australia work placements are an essential part of most postgraduate qualifications in Translation Studies as a way to guarantee graduates’ job-readiness. Work placements, however, are not always run ethically and efficiently. This research paper analyzes the pragmatic and theoretical aspects of professional placements in Translation Studies, and reports on work placements of five Masters students at the University of Western Australia. The students’ experiences were diverse and proved that safeguards need to be put in place for work placements to be successful tripartite collaborations between universities, trainees and hosts. Flexibility and students’ autonomy seemed to play an important part in the success of work placement arrangements. Both work supervisor and subject coordinator must be properly prepared for their tasks, perhaps taking guidance from their counterparts in vocational studies. Nonetheless, all students in these cases studies were confronted with real-life issues that translators have to routinely solve and this rapidly increased their job-readiness.